MARKETING COMMUNICATION STRATEGY IMPLEMENTED BY THE HOTEL AS AN EFFORT TO INCREASE VISITOR INTEREST DURING COVID-19 PANDEMIC - Yuary Farradia (Yayasan Education and Social Center, 2022)
In achieving success, they have prepared several marketing communication strategies before marketing their community products, increasingly attracting public attention. The purpose of this research is how marketing communication strategies are carried out to increase visitor interest during the Covid-19 pandemic period. The research method used in this study uses qualitative research with a descriptive approach and data collection techniques through interviews and documentation. The data analysis technique of this research was carried out after obtaining data through interviews and in-depth documentation. Then, this data is selected with important and irrelevant data from the collected data, analyzed in relation to each other to get provisional allegations and draw conclusions. This study indicates that marketing communications during the Covid-19 pandemic have referred to the 4Ps, namely Product, Price, Place, and Promotion. During the Covid-19 pandemic, hotels have implemented health protocols following government recommendations, intensively conducting sales calls and telemarketing, holding promotions every month, and collaborating with other parties to promote to companies, government agencies, and travel agents both offline travel agents to increase visitor interest